Antimicrobial peptide coatings for hydroxyapatite: electrostatic and covalent attachment of antimicrobial peptides to surfaces. Issue 126 (31st January 2017) - Townsend, Leigh; Williams, Richard L.; Anuforom, Olachi; Berwick, Matthew R.; Halstead, Fenella; Hughes, Erik; Stamboulis, Artemis; Oppenheim, Beryl; Gough, Julie; Grover, Liam; Scott, Robert A. H.; Webber, Mark; et al.
Abstract : The interface between implanted devices and their host tissue is complex and is often optimized for maximal integration and cell adhesion. However, this also gives a surface suitable for bacterial colonization. We have developed a novel method of modifying the surface at the material–tissue interface with an antimicrobial peptide (AMP) coating to allow cell attachment while inhibiting bacterial colonization. The technology reported here is a dual AMP coating. The dual coating consists of AMPs covalently bonded to the hydroxyapatite surface, followed by deposition of electrostatically bound AMPs. The dual approach gives an efficacious coating which is stable for over 12 months and can prevent colonization of the surface by both Gram-positive and Gram-negative bacteria.